YURIY SHEVEL’OV IN THE SPACE OF THE UKRAINIAN NATIONAL LINGUISTICS - Danylenko, A. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is written on occasion of anniversary of the known Ukrainian linguist and literary critic Yury Shevel’ov (Shereh); the problem of publications of labors of the Ukrainian scientist is broken from Diaspora in mainland Ukraine, the foreground jobs of propaganda of philological experience of researcher are certain.